The role of epidemiology and surveillance systems in the control of sexually transmitted diseases. Issue 5 (October 1996) - Catchpole, M A
Abstract : Surveillance and epidemiological studies are essential components of effective control programmes for sexually transmitted diseases. While other forms of basic biomedical research may add to our understanding of why an exposure or behaviour causes or prevents disease, only epidemiology allows the quantification of the magnitude of the exposure-disease relationship in humans. It is this measure of the association between risk and disease that is needed to inform rational policy on altering risk through intervention. Surveillance data are used both to determine the need for public health action and to assess the effectiveness of programmes: they are required for the setting of priorities, for planning and resource allocation, for the definition of population subgroups and risky behaviours for targeted interventions, for the development of disease prevention programmes, and for the evaluation of interventions. Data from surveillance systems and epidemiological studies can also inform diagnostic and therapeutic practice, and indicate areas for further research. Over the last 20 years chlamydia infections and viral agents have emerged as the major cause of STD in developed countries, and with this change in the aetiological mix of STD cases the focus of prevention and control of STDs has shifted from treatment and partner notification towards health education. In developing countries there is an urgent need for appropriate surveillance infrastructures, particularly now that there is evidence that STD control programmes, informed by surveillance data, can reduce HIV transmission at the population level. The importance of surveillance and epidemiology in the control of STDs is set to increase in the face of the changing pattern of sexually transmitted pathogens. The challenge to clinicians and epidemiologists is to work together in developing systems that will inform new approaches to control and prevention.